Who you gonna call? Oligarchic clans as a bottom-up force of neighborhood europeanization in Ukraine - Inna Melnykovska; Rainer Schweickert (Osteuropa-Inst., 2008)
This paper argues that, in the absence of a strong membership incentive within the European Neighborhood Policy (ENP), a top-down institutional convergence of CIS countries towards European standards – i.e. democracy and market economy – is unlikely to be successful. However, due to enlargement fatigue within the EU, the membership incentive is off the agenda for the CIS. Hence, the ENP has to initiate or to speed up a bottom-up institutional convergence by identifying bottom-up domestic forces that are willing and able to drive the convergence in a particular country. Ukraine, whose oligarchic clans are the main bottom-up forces behind institution building, is a case in point. After having supported the first wave of institutional reforms during the Orange Revolution, these bottom-up forces are facing great difficulties in forming sustainable coalitions for further institutional reforms. The paper shows that the EU could, by providing economic incentives rather than the membership incentive, exploit the strong business interests of the oligarchic clans in the EU markets and EU investment to motivate them to jointly drive institutional convergence from the bottom-up.
urn:nbn:de:0144-200712135162
Keywords: B15; D02; D72; F15; P33; P36; 330; Europeanization; institutional convergence; institution building; Orange revolution; oligarchic clans; Europäische Nachbarschaftspolitik; Institutioneller Wandel; Institutionelle Infrastruktur; Oligarchie; Ukraine; EU-Staaten